Effect of blood contamination on marginal adaptation of cold ceramic and MTA angelus: a scanning electron microscopic study - Fatemeh Mokhtari; Jalil Modaresi; Abbas Bagheri (BMC, 2023)
Abstract Background This study aimed to assess the effect of blood contamination on marginal adaptation of cold ceramic (CC) and mineral trioxide aggregate (MTA) Angelus using scanning electron microscopy (SEM). Methods This in vitro experimental study was conducted on 24 extracted single-rooted human teeth. After cleaning and shaping, the root canals were filled with lateral compaction technique. The apical 3 mm of the roots was cut, and cavities with 3 mm depth were created at the apex. The teeth were randomly assigned to two group (n = 12) for the application of CC and MTA Angelus as retrograde filling materials. CC and MTA Angelus were prepared by mixing the powder with blood, and applied in the cavities. After 24 h, their marginal adaptation to the canal walls was assessed by SEM. Data were statistically analyzed by t-test (alpha = 0.05). Results The mean marginal gap was 8.98 μm in the CC, and 16.26 μm in the MTA Angelus group; this difference was statistically significant (P < 0.001). Conclusions The present in vitro study revealed that following complete blood contamination of powder, CC showed significantly superior marginal adaptation than MTA Angelus as shown by SEM assessment.